PAKISTAN-RUSSIA MILITARY COOPERATION: CHALLENGES AND OPPORTUNITIES - Adeel Ahmed; Faisal; Ghulam Rasool (International Journal of Contemporary Issues in Social Sciences, 2023)
In the dynamic realm of 21st-century international relations, a profound transformation has emerged in the strategic partnership between Pakistan and Russia. This research delves into the intricate dynamics of military cooperation, shedding light on the challenges and opportunities that define this critical relationship. Pakistan’s strategic position in South Asia and Russia’s historical influence converge, presenting substantial potential for addressing shared threats and reinforcing regional stability, particularly in the context of counterterrorism efforts. The burgeoning collaboration between Pakistan and Russia unfolds a spectrum of opportunities for both countries. Furthermore, this research delves into the essence of military collaboration on the global stage within this partnership. It meticulously scrutinizes the potential impacts on the power diminuendos in the region, particularly within the context of the India-Pakistan rivalry. Yet, the path to fortifying military ties is fraught with obstacles. This paper offers an exhaustive analysis of the challenges faced by both countries as strive to expand collaboration. The research study provides a nuanced understanding of the Pakistan-Russia military partnership through a comprehensive investigation of the historical background, contemporary developments, and future prospects. It stands as a valuable resource for scholars, policymakers, and analysts keen on navigating the intricate terrain of opportunities and hurdles that delineate this evolving strategic alliance. In conclusion, the military cooperation between Pakistan and Russia serves as a pivotal element of the ever-evolving global geopolitical landscape, affording both nations a unique opportunity to leverage shared interests for the betterment of regional and global stability. This paper not only unravels the intricacies of the partnership but underscores the imperative to address the challenges that lie ahead in an ever-shifting global landscape.